Linguistic Landscape Analysis of Food Advertisement in Makassar - Nirwana, Nirwana; Sharma, Mani Ram (CV. Creative Tugu Pena, 2022)
The focus of this research is on Makassar's linguistic landscape of food advertisements. The study's goals are to determine the language used in food advertisements in Makassar city and to describe the roles of the Makassar language employed in food advertisements. This study uses the descriptive qualitative method. The data are analyzed based on Canoz and Gorter’s theory (2006). The findings show that English is the most frequently used language in food advertisements in the city center of Makassar. The other languages utilized in advertisements include Indonesian, English, Makassar, and Mandarin. This study also found the function of using English in advertisements is a promotional medium and the identity of each store. Additionally, using a foreign language has a trendy and stylish impact, which improves product quality, intrigues buyers, and attracts their attention. Even though many offers in advertisements are not understood by consumers, all of the functions indicated by all informants allude to the benefits of utilizing English in their product advertisements, notably the increased sales value. Keywords: Linguistic Lanscape Analysis, Analysis Food Advertisement, Analysis Advertisement